RNA expression profiles and regulatory networks in human right ventricular hypertrophy due to high pressure load - Chouvarine, Philippe; Photiadis, Joachim; Cesnjevar, Robert; Scheewe, Jens; Bauer, Ulrike M. M.; Pickardt, Thomas; Kramer, Hans-Heiner; Dittrich, Sven; Berger, Felix; Hansmann, Georg (iScience, 2021)
Right ventricular hypertrophy (RVH) occurs in high pressure afterload, e.g., tetralogy of Fallot/pulmonary stenosis (TOF/PS). Such RVH is associated with alterations in energy metabolism, neurohormonal and epigenetic dysregulation (e.g., microRNA), and fetal gene reprogramming in animal models. However, comprehensive expression profiling of competing endogenous RNA in human RVH has not been performed. Here, we unravel several previously unknown circular, long non-coding, and microRNAs, predicted to regulate expression of genes specific to human RVH in the non-failing heart (TOF/PS). These genes are significantly overrepresented in pathways related to regulation of glucose and lipid metabolism (SIK1, FABP4), cell surface interactions (THBS2, FN1), apoptosis (PIK3IP1, SIK1), extracellular matrix composition (CTGF, IGF1), and other biological events. This is the first unbiased RNA sequencing study of human compensated RVH encompassing coding and noncoding RNA expression and predicted sponging of miRNAs by non-coding RNAs. These findings advance our understanding of adaptive RVH and highlight future therapeutic targets.
CRIS-Team WoS Importer:2021-04-16